A pilot-scale anaerobic moving-bed biofilm reactor with PVA gel beads as media for the treatment of fish canning industry wastewater. Issue 2 (12th April 2022) - Jirasaranporn, Akarawin; Jantharadej, Krittayapong; Wongwailikhit, Kritchart; Chawengkijwanich, Chamorn; Lohwatcharin, Jenyuk; Suwannasilp, Benjaporn Boonchayaanant
Abstract: This research aims to investigate the performance of a pilot-scale anaerobic moving-bed biofilm reactor (AnMBBR) using PVA gels as media for the treatment of real wastewater from a fish canning factory. The chemical oxygen demand (COD) removal efficiencies at different organic loading rates (OLRs) were investigated at 3.0, 4.3, 6.5, and 8.7 kg COD/m 3 day by adjusting the flow rates to 350, 500, 750 and 1, 000 L/d, respectively. The soluble COD removal efficiencies of the system at flow rates of 350, 500, 750, and 1, 000 L/d were 81.0 ± 12.4%, 76.8 ± 8.2%, 74.7 ± 6.2%, and 70.6 ± 12.4%, respectively. According to the residence time distribution (RTD) tests at the highest and lowest flow rates, the mean residence times of both flow rates were significantly higher than the theoretical residence time, indicating very strong external recirculation inside the AnMBBR. The results suggest a 3-pass flow pattern through the AnMBBR. From 16S rRNA gene amplicon sequencing (MiSeq, Illumina) and scanning electron microscopy (SEM) analysis, Methanosaeta, acetoclastic methanogens, were the predominant microorganisms in the system. Most of the microorganisms were located within a 1.994 ± 0.266 mm depth from the PVA gel surface, with two distinct layers. HIGHLIGHTS: The average sCOD removal efficiencies were above 70% for all OLRs (3.0–8.7 kg COD/m 3 day). The AnMBBR has a 3-pass flow pattern due to strong external recirculation. Methanosaeta, acetoclastic methanogens, were predominant in the system. Graphical Abstract